Plasma flow velocity measured by Swarm and inferred from SuperDARN global-scale convection maps - A.V. Koustov; H. Fast; J.K. Burchill; L. Lomidze; A. Kouznetsov; M. Ghalamkarian Nejad (Advances in Space Research, 2025)

Local inflammation at the salmon louse (Lepeophtheirus salmonis) attachment site contributes to copepodid rejection in coho salmon (Oncorhynchus kisutch) - Lene Sveen; Mark D. Fast; Torstein Tengs; Rachel A. Kline; Judit Aguilar Marti; Dominic Kurian; Gerrit Timmerhaus; Marianne Vaadal; Ross D. Houston; James E. Bron; Sean J. Monaghan; Haitham H. Mohammed; et al. (Cell and Tissue Research, 2025)
The study investigates the susceptibility of Atlantic salmon ( Salmo salar ) and Pacific salmon species (pink salmon, Oncorhynchus gorbuscha ; coho salmon, Oncorhynchus kisutch ; and chum salmon, Oncorhynchus keta ) to the parasitic salmon lice ( Lepeophtheirus salmonis ). The research had two main objectives: to characterize the morphology of the scaly skin in four salmonid species and to compare the cellular response at the louse attachment site in coho salmon and Atlantic salmon. Three consecutive challenge trials were conducted, with successful louse infestation only achieved across all four species in the third trial using mild anesthesia with tricaine methanesulfonate. Skin and fin samples were collected at 12, 24, 36, 48, 60, and 168 h post-infestation (hpi) for histological, proteomic, and spatial transcriptomic analyses. Results showed that chum salmon had significantly higher mucous cell coverage (30–40%) in the epithelium of scaly skin compared to Atlantic salmon (10%). At the louse attachment site in coho salmon, there was a greater influx of inflammatory cells at 36–48 hpi compared to Atlantic salmon. Proteomic analysis at 12 hpi and 36 hpi in coho salmon showed upregulation of neutrophil degranulation and formyl-methionyl-leucyl-phenylalanine signaling. Additionally, spatial transcriptomics at the attachment site showed local upregulation of inflammatory gene markers. These findings suggest that coho salmon mount a rapid and large-scale inflammatory response driven by neutrophils to louse attachment within the first 48 hpi. Overall, the study emphasizes the significance of local changes at the host-parasite interface for resistance mechanisms against salmon lice.

Circulation of West Nile virus and Usutu virus in birds in Germany, 2021 and 2022 - Franziska Schopf; Balal Sadeghi; Felicitas Bergmann; Dominik Fischer; Ronja Rahner; Kerstin Müller; Anne Günther; Anja Globig; Markus Keller; Rebekka Schwehn; Vanessa Guddorf; Maximilian Reuschel; et al. (Infectious Diseases, 2025)

An aquaculture risk model to understand the causes and consequences of Atlantic Salmon mass mortality events: A review - Zaman Sajid; A. Kurt Gamperl; Christopher C. Parrish; Stefanie M. Colombo; Javier Santander; Charles Mather; Barbara Neis; Ingunn Marie Holmen; Ramón Filgueira; Cynthia H. McKenzie; Lissandra Souto Cavalli; Mohamed Jeebhay; et al. (Reviews in Aquaculture, 2024)
Mass mortality events (MMEs) are defined as the death of large numbers of fish over a short period of time. These events can result in catastrophic losses to the Atlantic salmon aquaculture industry and the local economy. However, they are challenging to understand because of their relative infrequency and the high number of potential factors involved. As a result, the causes and consequences of MMEs in Atlantic salmon aquaculture are not well understood. In this study, we developed a structural network of causal risk factors for MMEs for aquaculture and the communities that depend on Atlantic salmon aquaculture. Using the Interpretive Structural Modeling (ISM) technique, we analysed the causes of Atlantic salmon mass mortalities due to environmental (abiotic), biological (biotic) and nutritional risk factors. The consequences of MMEs were also assessed for the occupational health and safety of aquaculture workers and their implications for the livelihoods of local communities. This structural network deepens our understanding of MMEs and points to management actions and interventions that can help mitigate mass mortalities. MMEs are typically not the result of a single risk factor but are caused by the systematic interaction of risk factors related to the environment, fish diseases, feeding/nutrition and cage‐site management. Results also indicate that considerations of health and safety risk, through pre‐ and post‐event risk assessments, may help to minimize workplace injuries and eliminate potential risks of human fatalities. Company and government‐assisted socio‐economic measures could help mitigate post‐mass mortality impacts. Appropriate and timely management actions may help reduce MMEs at Atlantic salmon cage sites and minimize the physical and social vulnerabilities of workers and local communities.

Applying genetic technologies to combat infectious diseases in aquaculture - Nicholas A. Robinson; Diego Robledo; Lene Sveen; Rose Ruiz Daniels; Aleksei Krasnov; Andrew Coates; Ye Hwa Jin; Luke T. Barrett; Marie Lillehammer; Anne H. Kettunen; Ben L. Phillips; Tim Dempster; et al. (Reviews in Aquaculture, 2023)
Disease and parasitism cause major welfare, environmental and economic concerns for global aquaculture. In this review, we examine the status and potential of technologies that exploit genetic variation in host resistance to tackle this problem. We argue that there is an urgent need to improve understanding of the genetic mechanisms involved, leading to the development of tools that can be applied to boost host resistance and reduce the disease burden. We draw on two pressing global disease problems as case studies—sea lice infestations in salmonids and white spot syndrome in shrimp. We review how the latest genetic technologies can be capitalised upon to determine the mechanisms underlying inter‐ and intra‐species variation in pathogen/parasite resistance, and how the derived knowledge could be applied to boost disease resistance using selective breeding, gene editing and/or with targeted feed treatments and vaccines. Gene editing brings novel opportunities, but also implementation and dissemination challenges, and necessitates new protocols to integrate the technology into aquaculture breeding programmes. There is also an ongoing need to minimise risks of disease agents evolving to overcome genetic improvements to host resistance, and insights from epidemiological and evolutionary models of pathogen infestation in wild and cultured host populations are explored. Ethical issues around the different approaches for achieving genetic resistance are discussed. Application of genetic technologies and approaches has potential to improve fundamental knowledge of mechanisms affecting genetic resistance and provide effective pathways for implementation that could lead to more resistant aquaculture stocks, transforming global aquaculture.

Small Molecule Specific Run Acceptance, Specific Assay Operation, and Chromatographic Run Quality Assessment: Recommendation for Best Practices and Harmonization from the Global Bioanalysis Consortium Harmonization Teams - Eric J. Woolf; Stuart McDougall; Douglas M. Fast; Maristela Andraus; Matthew Barfield; Michael Blackburn; Ben Gordon; David Hoffman; Noriko Inoue; Gabriel Marcelin-Jimenez; Amy Flynn; Richard LeLacheur; et al. (The AAPS Journal, 2014)

Combinatorial effects of administration of immunostimulatory compounds in feed and follow‐up administration of triple‐dose SLICE ® ( e mamectin benzoate) on A tlantic salmon, S almo salar L., infection with L epeophtheirus salmonis - J Poley; S L Purcell; O O Igboeli; A Donkin; H Wotton; M D Fast (Journal of Fish Diseases, 2013)
Several immunostimulatory feed additives have shown the ability to induce protective responses in A tlantic salmon to infection with L epeophtheirus salmonis . However, even the most encouraging results rarely surpass a 50% protective index in the host. That fact coupled with the well‐documented limitations of single‐therapy strategies in the effective management of parasitic infections generally make it imperative to identify therapies that can be combined in an integrated pest management approach for sea lice. With this in mind, we hypothesized that immunostimulatory feeds could enhance the protection provided by SLICE ® emamectin benzoate ( EMB ). To test this hypothesis, Atlantic salmon were fed one of two different immunostimulatory feeds ( CpG ODN or A quate ® ) for c . 7 weeks, challenged with L . salmonis copepodids early within that immunostimulatory feed period and then placed on a triple‐dose (150 μg kg −1 ) feed of SLICE ® for 1 week following the completion of the immunostimulatory feeding period. CpG ODN (2 mg kg −1 ) and the commercial yeast extract ( A quate ® 0.2%) inclusion in feeds were able to successfully induce inflammatory gene expression (interleukin‐1β) in the head kidneys of infected fish at 13 and 26 days post‐exposure ( DPE ), and 13 DPE , respectively. Lice burdens were lower on fish fed CpG ODN (18%) or A quate ® (19%) diets; however, due to variability, these were not statistically significant over time. Despite no statistically significant reductions in lice numbers, by 33 DPE fish on immunostimulatory feeds had significantly reduced cortisol levels when compared to infected fish on control diet. Cortisol levels in fish receiving an immunostimulatory diet were no different from initial baseline levels prior to infection, whereas the levels in control diet fish were significantly elevated from all other time points. Despite the positive effects on infection of fish fed immunostimulatory feeds, no synergism was observed with follow‐up treatment with SLICE ® . In fact, highest survival of lice was observed in fish with prior immunostimulation.

Immunostimulation of S almo salar L., and its effect on L epeophtheirus salmonis (Krøyer) P ‐glycoprotein mRNA expression following subsequent emamectin benzoate exposure - O O Igboeli; S L Purcell; H Wotton; J Poley; J F Burka; M D Fast (Journal of Fish Diseases, 2013)
Control of sea lice, L epeophtheirus salmonis , on farmed A tlantic salmon, S almo salar , relies heavily on chemotherapeutants. However, reduced efficacy of many treatments and need for integrated sea lice management plans require innovative strategies. Resistance to emamectin benzoate (EMB), a major sea lice parasiticide, has been linked with P‐glycoprotein (P‐gp) expression. We hypothesized that host immunostimulation would complement EMB treatment outcome. Lepeophtheirus salmonis ‐infected Atlantic salmon were fed immunostimulatory or control feeds. Sea lice were collected for 24‐h EMB bioassays 1 and 2 weeks prior to commencement of EMB treatment of the fish. Two weeks after cessation of immunostimulant‐treated feed, EMB was administered at 150 μg kg −1 fish biomass for 7 days. The bioassay revealed stage, gender and immunostimulant‐related differences in EMB EC 50 . Sea lice attached to salmon with a history of immunostimulation exhibited significantly greater survival than those on control feeds, despite similar levels of EMB in host tissues. Lepeophtheirus salmonis from salmon with a history of immunostimulation also exhibited higher P‐gp mRNA expression as well as greater survivability compared to controls. Administration of immunostimulants prior to EMB treatment caused increased expression of P‐gp mRNA which could have consequently caused decreased efficacy of the parasiticide.

Generation of Priority Research Questions to Inform Conservation Policy and Management at a National Level - MURRAY A. RUDD; KAREN F. BEAZLEY; STEVEN J. COOKE; ERICA FLEISHMAN; DANIEL E. LANE; MICHAEL B. MASCIA; ROBIN ROTH; GARY TABOR; JISELLE A. BAKKER; TERESA BELLEFONTAINE; DOMINIQUE BERTEAUX; BERNARD CANTIN; et al. (Conservation Biology, 2011)
Integrating knowledge from across the natural and social sciences is necessary to effectively address societal tradeoffs between human use of biological diversity and its preservation. Collaborative processes can change the ways decision makers think about scientific evidence, enhance levels of mutual trust and credibility, and advance the conservation policy discourse. Canada has responsibility for a large fraction of some major ecosystems, such as boreal forests, Arctic tundra, wetlands, and temperate and Arctic oceans. Stressors to biological diversity within these ecosystems arise from activities of the country's resource‐based economy, as well as external drivers of environmental change. Effective management is complicated by incongruence between ecological and political boundaries and conflicting perspectives on social and economic goals. Many knowledge gaps about stressors and their management might be reduced through targeted, timely research. We identify 40 questions that, if addressed or answered, would advance research that has a high probability of supporting development of effective policies and management strategies for species, ecosystems, and ecological processes in Canada. A total of 396 candidate questions drawn from natural and social science disciplines were contributed by individuals with diverse organizational affiliations. These were collaboratively winnowed to 40 by our team of collaborators. The questions emphasize understanding ecosystems, the effects and mitigation of climate change, coordinating governance and management efforts across multiple jurisdictions, and examining relations between conservation policy and the social and economic well‐being of Aboriginal peoples. The questions we identified provide potential links between evidence from the conservation sciences and formulation of policies for conservation and resource management. Our collaborative process of communication and engagement between scientists and decision makers for generating and prioritizing research questions at a national level could be a model for similar efforts beyond Canada.

Chemical Ozone Loss in the Arctic Winter 1994/95 as Determined by the Match Technique - M. Rex; P. Von Der Gathen; G.O. Braathen; N.R.P. Harris; E. Reimer; A. Beck; R. Alfier; R. Krüger-carstensen; M. Chipperfield; H. De Backer; D. Balis; F. O'Connor; et al. (Journal of Atmospheric Chemistry, 1999)

A Study of Ozone Laminae Using Diabatic Trajectories, Contour Advection and Photochemical Trajectory Model Simulations. - S. J. Reid; M. Rex; P. Von Der Gathen; I. Fløisand; F. Stordal; G. D. Carver; A. Beck; E. Reimer; R. Krüger-Carstensen; L. L. De Haan; G. Braathen; V. Dorokhov; et al. (Journal of Atmospheric Chemistry, 1998)

Residues of chlorinated phenols and phenoxy acid herbicides in the urine of Arkansas children - Robert H. Hill; Teresa To; James S. Holler; Douglas M. Fast; S. Jay Smith; Larry L. Needham; Suzanne Binder (Archives of Environmental Contamination and Toxicology, 1989)